Arduino based solar tracking system - Sathis, Vatumalai (2016)
This thesis proposes the dual axis solar tracker for optimum solar cell implementation using dc-dc boost converter controlled by fuzzy logic controller with the maximum power point tracking (MPPT) method. The objectives of this project are to track and optimize the maximum output power of the solar panel by designing and implementing the fuzzy logic controller using microcontroller as well as to regulate the output voltage of the solar panel using dc-dc boost converter. The system includes a solar panel, DC-DC boost converter, the fuzzy logic controller implemented on Arduino Uno for controlling on/off time of MOSFET of the boost converter, voltage divider and optocoupler circuit as a driver for MOSFET. Tracking and detecting the angle of the sun to locate the surface plate of solar cell at the position and the angle where it can get maximum amount of energy. The solar panel must have sensors that can detect the position of the sun and dc motors act as free moving neck to make it easier to move freely depending on the angle detected. The light dependent resistor (LDR) will be used as sun tracking. The photocell panel will detect the existing of sun and the surface plate of photocell panel will move horizontal and vertical axis depending on the value of LDR detected to follow the angular degree of sun in order to get maximum and best result of absorbing energy. Moreover, this project presents a fuzzy logic real time code in Arduino language for ATmega328 microcontroller at Arduino Uno board. The result obtained from the Arduino coding is the variation of duty cycle of PWM signal according to the voltage of solar panel. The final result obtained from dc-dc boost converter showed that the output voltage has been regulated. Overall, the designed system increases the efficiency of the solar panel based on experimental results.